Interrelationship of interleukin 6, C-reactive protein and Chlamydia pneumoniae IgG antibodies in patients with acute coronary syndromes - Burazor Ivana; Vojdani Aristo; Burazor Mirko (Vojnosanitetski Pregled)
Background/Aim. Inflammation due to infection could be associated with the development of acute coronary syndromes, clinical manifestations of ongoing atherosclerosis in vessel walls. Our aim was determine whether interleukin 6, C-reactive protein and Chlamydia pneumoniae IgG antibodies are connected with the development of acute coronary syndromes, to evaluate their interrelationship and to examine whether they are predictive of new events and mortality. Methods. This prospective study included 211 subjects, of whom 111 were patients with acute coronary syndromes (60% male, mean age 59.42 years) and 100 were healthy controls (58% male, mean age 59.03 yuears). Blood samples were taken for analysis on admission, before the application of the therapy. Interleukin 6, high sensitivity C-reactive protein and Chlamydia pneumoniae IgG antibodies were measured, in a follow-up period of 30 days. Results. Levels of interleukin 6 (p < 0.001) and C-reactive protein (p < 0.001) were significantly higher among the patients with acute coronary syndromes than among controls. Chronic infection caused by Chlamydia pneumoniae was present in 72% of patients and in 22% of healthy controls (p < 0.001). There was a correlation between interleukin 6 and C-reactive protein, C-reactive protein and Chlamydia pneumoniae but not between Chlamydia pneumoniae and interleukin 6. Higher levels of interleukin 6 and C-reactive protein were seen with increasing body mass index, smoking exposure, presence of hypertension and diabetes, and decreasing ejection fraction. The patients with ST-segment elevation had higher examined markers than the patients without ST-segment elevation. Interleukin 6 and C-reactive protein were independently related to the clinical outcome. Conclusion. Interleukin 6, C-reactive protein and Chlamydia pneumoniae infection are connected with the development of acute coronary syndromes and may reflect a clinical outcome of the disease.